Pelvic fractures in severely injured children: Results from the TraumaRegister DGU. Issue 35 (August 2018) - Zwingmann, Jörn; Lefering, Rolf; Maier, Dirk; Hohloch, Lisa; Eberbach, Helge; Neumann, Mirjam; Strohm, Peter. C.; Südkamp, Norbert P.; Hammer, Thorsten
Abstract : Abstract: Injuries in the pelvic region in children and adolescents are very rare and often associated with a high energy trauma. Aim of this prospective multicenter study was, by analyzing the data from the TraumaRegister Deutsche Gesellschaft für Unfallchirurgie (TR-DGU), to evaluate any correlation between the severity of pelvic fractures and resulting mortality in different age groups. These study findings are based on a large pool of data retrieved from the prospectively-setup pelvic trauma registry established by the German Trauma Society (DGU) and the German Section of the Association for Osteosynthesis/Association for the Study of Internal Fixation (AO/ASIF) International in 1991. The registry provides data on all patients suffering pelvic fractures within a 14-year time frame at any 1 of the 23 level 1 trauma centers contributing to the registry. The analysis covers 4 age groups ranging from 0 to 17 years, covering different factors regarding pelvic fractures and their treatment. We identified a total of 9684 patients including 1433 pelvic fractures in children aged ⩽17 years. Those patients were divided into 4 subgroups according to the patients' age (groups A–D) and according to the fracture severity (group 1 =  Abbreviated Injury Scale (AIS) score pelvis ⩽2, and group 2 = AIS pelvis ≥3). The mortality in group 1 was 8.8% with a RISC (Revised Injury Severity Score) II of 8.6%, standard mortality rate (SMR) of 1.02 and 7.2% in group 2 with an RISC II of 9.9% (SMR 0.73). In pelvic factures of Type A (Tile classification of pelvic fractures), an SMR of 0.76 was recorded, in Type B fractures the SMR was 0.65, and in Type C fractures 0.79. Severe pelvic injuries (AIS pelvis ≥2) were associated with a higher rate of whole body computer tomograph (CT) scans (1–5 years: 80%, 6–10 years 81.8%, 11–14 years 84.7%, and 15–17 years 85.6%). The rate of pelvic surgery rose with the pelvic injury's severity (AIS 2: 7.6%, AIS 3: 35%, AIS 4: 65.6%, AIS 5 61.5%). We observed higher rates of preclinical and initial clinical hypotension defined as Riva-Rocci (RR) <90 mmHG) as well as of preclinical fluid application in all age groups. The presence of a pelvic injury was associated with a higher rate of severe abdominal injuries with an AIS of ≥3 (25.1% vs. 14.6%) and of severe thorax injuries with an AIS≥3 (43.6% vs. 28.6%). We have been able to analyze an enormous number of pelvic fractures in children and adolescents including different age groups by relying on data from the TR-DGU. Mortality seems to be associated with the severity of the pelvic injury, but is lower than the RISC II score's prognosis.